Removal of a Periarticular Cyst of the Hip Joint Using an Ultrasoundbased Minimally Invasive Technique — A Case Report - Konarski, Wojciech; Poboży, Tomasz (Current Medical Imaging, 2022)
Introduction: Cystic lesions protruding into surrounding anatomical structures may decrease quality of life. Case Presentation: In our case, the cyst was located periarticularly which indicated a potential need for open surgery. We used ultrasound-based minimally invasive arthroscopy technique. A 39-year-oldwoman’s ultrasonographic examination revealed delamination of the acetabular labrum and periarticular cyst located extra-articularly, compressing the iliopsoas muscle. The ultrasound-guided complete removal of the cyst was performed using a shaver blade placed into its lumen through the skin incision. The acetabular labral tear was treated with a classic arthroscopy procedure. 5 weeks after the surgery, the patient reported no pain and no functional impairment was detected. Conclusion: A well-known ultrasound diagnostic technique can save patients from more invasive procedures and can be beneficial for the surgeons.
Keywords: shaver